2016
DOI: 10.3945/ajcn.115.117440
|View full text |Cite
|
Sign up to set email alerts
|

Administration of resveratrol for 5 wk has no effect on glucagon-like peptide 1 secretion, gastric emptying, or glycemic control in type 2 diabetes: a randomized controlled trial

Abstract: In patients with diet-controlled type 2 diabetes, 5 wk of twice-daily 500 mg-resveratrol supplementation had no effect on GLP-1 secretion, glycemic control, gastric emptying, body weight, or energy intake. Our observations do not support the use of resveratrol for improving glycemic control. This trial was registered at www.anzctr.org.au as ACTRN12613000717752.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 31 publications
3
79
1
Order By: Relevance
“…This result is in accordance with several other human studies also not observing effects of resveratrol supplementation on fasting lipid and glucose concentrations [3]. Further, a study on type 2 diabetic individuals did not find an effect on postprandial glucose concentrations [4]. Nevertheless, trans -resveratrol might affect other parameters related to cardiovascular health, such as vascular endothelial dysfunction.…”
Section: Introductionsupporting
confidence: 91%
“…This result is in accordance with several other human studies also not observing effects of resveratrol supplementation on fasting lipid and glucose concentrations [3]. Further, a study on type 2 diabetic individuals did not find an effect on postprandial glucose concentrations [4]. Nevertheless, trans -resveratrol might affect other parameters related to cardiovascular health, such as vascular endothelial dysfunction.…”
Section: Introductionsupporting
confidence: 91%
“…On the other hand, in patients with metabolic syndrome, RSV supplementation did not have any effect on systolic and diastolic blood pressure [35,36]. Furthermore, in a recent randomized trial in type II diabetes patients, ingestion of 500mg/day of RSV for 5 weeks failed to show any beneficial effects [37]. Majority of clinical trials were centered on the therapeutic effects of RSV supplementation, whereas studies based on preventive approaches are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…These apparent unsuccessful studies also may be explained by variability between volunteers (age, body weight, nutrition, severity of diabetes) and/or duration of treatments [119]. In agreement with this hypothesis, another study of patients with metabolic syndrome treated the patients with 1500 mg/day of resveratrol for 90 days (~13 weeks) and revealed a significant reduction in body weight and insulin secretion [137]. Additionally, Goh et al [138] showed improvement of insulin sensitivity via SIRT1 through 3000 mg of resveratrol for 12 weeks in type-2 diabetic patients.…”
Section: Potential Of Natural Products With Antioxidant Effects Fomentioning
confidence: 97%
“…This is a problem because it has generated serious doubts about the potential usefulness of these substances, particularly for dietary prevention strategies [133,134,135,136]. For instance, Thazhath et al [137] have recently demonstrated that 1000 mg/day resveratrol in diet-controlled type-2 DM patients for five weeks did not change body weight, glycemic control or GLP-1 secretion. Similar data were also obtained by Poulsen et al [132], who gave 1500 mg/day of resveratrol for four weeks to obese patients and found no effects on metabolic biomarkers, blood pressure or resting energy expenditure.…”
Section: Potential Of Natural Products With Antioxidant Effects Fomentioning
confidence: 99%